Clinical and endoscopic spectrum of upper gastrointestinal manifestations in HIV patients - Ravikumar, VN; Rudresh, K; Jalihal, U; Satish, R; Manjunath, R (Kathmandu University Medical Journal, 2010)
Background: Human Immunodeficiency Virus (HIV) infected patient frequently report upper gastrointestinal (GI) symptoms; however their prevalence and diagnostic approach is not well known. Objective: The objective of this study was to study clinical, endoscopic and histopathological changes in HIV infected patients with upper GI symptoms and their correlation with CD4 count. Materials and methods: We evaluated 50 HIV infected patients who presented to M.S. Ramaiah hospital with upper GI symptoms. All patients answered questionnaire assessing upper GI symptoms and underwent upper GI endoscopy. Mucosal biopsy was taken wherever mucosal abnormality seen. Results: In our study, the mean age of patients was 40.98 yrs, of which 80% were males. Vomiting (36%), epigastric pain (36 %), weight loss (34 %) and anorexia (34%) were the predominant symptoms. Esophagogastroduodenoscopy (EGD) findings revealed- Oesophageal candidiasis in 28.0%, esophagitis in 22.0%, gastritis in 20.0 %, duodenitis in 14 %, normal upper GI mucosa in 18 % patients. Oesophageal candidiasis was the most common finding on histopathological examination and the mean CD4 count was 157.92 cells/μl. Conclusion: Vomiting, epigastric pain, weight loss and anorexia were most frequent symptoms. Oral candidiasis was the most common oral lesion. Oesophageal candidiasis, oesophagitis and oesophageal ulcers were the common findings on EGD. Patient with CD4 count less than 200cells/μl had more frequent upper GI mucosal involvement than in patients with CD4 count more than 200. Majority of the patients with GI symptoms had upper GI mucosal changes and opportunistic infections. Thus endoscopic and histopathological evaluation is advisable for the early diagnosis and treatment of upper GI complications in patients with HIV infection. Key words: AIDS; Oesophageal candidiasis; Esophagogastroduodenoscopy; HIV; Upper gastrointestinal symptoms. DOI: 10.3126/kumj.v8i1.3217 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 25-28